PERFORMANCE OF A NEWLY INSTALLED DEALERSHIP OF AGRICULTURAL MACHINERY AND IMPLEMENTS IN BOA VISTA-RR - da Silva, Edgley Soares; Albuquerque, Matheus de Lira; da Silva, Emerson de Souza; Monteiro Neto, João Luiz Lopes; Cruz, Ana Bárbara de Souza; Reyes, Veronica Nathaly Arevalo; Gonçalves, Anderson Carlos de Melo (Seven Editora, 2026)
This study analyzes the commercial and operational performance of a newly established dealership for agricultural machinery and implements in Boa Vista (RR), aiming to evaluate sales behavior, customer profile, average purchases per customer, and monthly revenue in the first year of operation. A descriptive case study with quantitative approach was conducted: administrative data from the 2023 fiscal year were collected and KPIs were applied to measure commercial efficiency and growth potential. The main results show that, among 25 clients served, 31 machines/implements were sold, with an average of 1.24 purchases per client, concentrated in grain farming and cattle ranching activities. Monthly sales variability reflects local seasonality. The analysis allowed us to conclude that the dealership's operation demonstrates immediate economic and strategic viability in the Roraima market. The company achieved a satisfactory initial sales volume, selling 31 machines/implements to 25 clients during its first year. This result is considered positive because it occurred in a new market, in the penetration phase, and which is experiencing a challenging national scenario in the agribusiness segment.